THE INFLUENCE OF EMPLOYEE ADDITIONAL INCOME (TPP) AND ORGANIZATIONAL JUSTICE EMPLOYEE PERFORMANCE AT THE REGIONAL PERSONNEL AND HUMAN RESOURCE DEVELOPMENT AGENCY (BKPSDM) OF WAJO REGENCY - Aminah, Sitti; Ismail, Imran (Ridwan Institute, 2025)
The purpose of this study was to determine and analyze the effect of additional employee income and organizational justice on employee performance at the Office of the Human Resources Development and Personnel Agency (BKPSDM) of Wajo Regency. The sample in this study is the total population, which is 43 respondents. Data collection techniques are carried out through observation, documentation and questionnaires. The results of the data analysis as seen in the table show that according to the perception of respondents in general, Organizational Justice at the Bureau of Personnel and Human Resource Development Agency is included in the very good criteria of the ideal score with the number of scores obtained 1451 with details of 10 indicators. The regression model in this research is suitable to be used to predict employee performance based on the input of additional variables of employee income, organizational fairness, and other variables outside this research model. The research shows that additional income and organization justice have a simultaneous and positive effect on employees' performance. The findings can inform policymakers and organizational leaders in designing effective compensation and management strategies that foster a positive work environment and improve employee outcomes. Lastly, qualitative research methods, such as interviews or focus groups, could be employed to gain deeper insights into employee perceptions and experiences regarding additional income, enriching the understanding of these dynamics in the workplace.